MODEL OLAHRAGA KEBUGARAN JASMANI DI MASA PENDEMI COVID-19 - Faiz Hifdzullah (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
This study aims to find out (1) whether exercise affects physical fitness in the future; (2) whether the pattern of exercise before the emigrant period affects physical fitness after the period of emigrant; (3) whether socioeconomics affect physical fitness in the future of emigrants; (4) whether the educational background affects physical fitness in the future of the emigrant. The formulation of the problem in research is: (1) whether regular exercise can maintain physical fitness in the future; (2) whether the pattern of exercise before the period of emigrant affects physical fitness; (3) whether socioeconomics affect physical fitness;(4) whether the educational background affects physical fitness. This research uses descriptive research methods that use survey research methods. This study takes the population from the public, because this coronavirus does not see the age affected, meets the classification of the characteristics to be studied, namely having a lifespan in the phase (15-63 years).Based on the results of research and previous discussions of models by physical fitness traders during the Covid-19 pandemic, it is known that good results with a percentage of 30%, in the moderate category by 33%, in the category of less than 33% and in the category of very good 3%. Based on these results can be interpreted pandemic circumstances have an impact on a person's physical fitness assessed from his physical activity.